2022
DOI: 10.1186/s13287-022-02845-9
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific regulation of signalling pathways to differentiate pluripotent stem cells to cardiomyocytes with ventricular lineage

Abstract: Background Pluripotent stem cells (PSCs) can be an ideal source of differentiation of cardiomyocytes in vitro and during transplantation to induce cardiac regeneration. However, differentiation of PSCs into a heterogeneous population is associated with an increased incidence of arrhythmia following transplantation. We aimed to design a protocol to drive PSCs to a ventricular lineage by regulating Wnt and retinoic acid (RA) signalling pathways. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…It was informed from the supplier that hiPSC-CMs differentiated using the kit become more ventricular over time. It was also suggested that Wnt signaling modulation of hiPSCs leads to predominant differentiation toward the ventricular lineage [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was informed from the supplier that hiPSC-CMs differentiated using the kit become more ventricular over time. It was also suggested that Wnt signaling modulation of hiPSCs leads to predominant differentiation toward the ventricular lineage [ 36 ].…”
Section: Methodsmentioning
confidence: 99%